Impact of Molecular and Crystal Structure on the Melting Points in Halo-Substituted Phenyl-Quinazolinones - Ivica Đilović; Nenad Judaš; Mario Komar; Maja Molnar; Marta Počkaj; Tomislav Balić (Crystals)
Three halo-substituted phenyl-quinazolinone derivatives were prepared and structurally characterized [1 = 3-(4-chlorophenyl)-6-iodo-2-methylquinazolin-4(3H)-one, 2 = 6-iodo-3-(4-methoxyphenyl)-2-methylquinazolin-4(3H)-one, and 3 = 7-chloro-2-methyl-3-[4-(trifluoromethoxy)phenyl]quinazolin-4(3H)-one)] in order to explore the relationship between structure and melting point in this group of compounds. Depending on the compound, molecules are interconnected by weak π∙∙∙π interactions, have I···Cl or Cl···Cl halogen bonding, or primarily form C–H∙∙∙N, C–H∙∙∙O, and π∙∙∙π interactions (no halogen bonding). The presence of the OCF3 group leads to interactions between fluorine atoms that are shorter than the sum of the van der Waals radius for fluorine, suggesting that these interactions contribute to the overall lattice energy. The sequence of melting points cannot be fully explained by intermolecular interactions present in the solid state (enthalpy factor). To address this, a concept related to entropy called the functional group rotation influence, which relates to a decrease in fusion entropy caused by the rotational freedom of polyatomic groups, was introduced. Analysis of previously synthesized 3-phenylquinazolinones showed that the compounds with the highest melting point are the quinazoline-substituted and phenyl-nitro-substituted ones. Among halo-phenyl-substituted compounds, the melting point follows the sequence ortho < meta < para. Regarding the halogen atom type, the order of melting points is Cl ≈ Br > F > I for enantiopure and Br > I ≈ Cl > F for racemic compounds. Also, the melting point order correlates to halogen bond energy (I > Br > Cl > F) only when the geometry and energy of these interactions are favorable.